2021
DOI: 10.1016/j.molcel.2021.06.017
|View full text |Cite
|
Sign up to set email alerts
|

An mTORC1-GRASP55 signaling axis controls unconventional secretion to reshape the extracellular proteome upon stress

Abstract: Summary Cells communicate with their environment via surface proteins and secreted factors. Unconventional protein secretion (UPS) is an evolutionarily conserved process, via which distinct cargo proteins are secreted upon stress. Most UPS types depend upon the Golgi-associated GRASP55 protein. However, its regulation and biological role remain poorly understood. Here, we show that the mechanistic target of rapamycin complex 1 (mTORC1) directly phosphorylates GRASP55 to maintain its Golgi localizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 113 publications
2
55
0
2
Order By: Relevance
“…SARS-CoV-2 infection down-regulates GRASP55 but not its homolog GRASP65. GRASP55 has been shown to play a crucial role in various stress responses (Ireland et al, 2020b; Nüchel et al, 2021; Zhang and Wang, 2018, 2020), while GRASP65 functions more in cell migration and apoptosis (Ahat et al, 2019; Bisel et al, 2008; Lane et al, 2002). In this study, we found that GRASP55 plays a vital role in viral infection, most likely related to its function in Golgi structure formation.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 infection down-regulates GRASP55 but not its homolog GRASP65. GRASP55 has been shown to play a crucial role in various stress responses (Ireland et al, 2020b; Nüchel et al, 2021; Zhang and Wang, 2018, 2020), while GRASP65 functions more in cell migration and apoptosis (Ahat et al, 2019; Bisel et al, 2008; Lane et al, 2002). In this study, we found that GRASP55 plays a vital role in viral infection, most likely related to its function in Golgi structure formation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, catabolic processes such as autophagy initiation and lysosome biogenesis are inhibited via mTORC1-dependent phosphorylation of Unc-51 related kinases (ULK) and transcription factors EB and E3 (TFEB and TFE3) [ 118 , 119 ]. Phosphorylation of these as well as other substrates enable mTORC1 to affect metabolic processes occurring both at the lysosome and in other compartments, including ribosome biogenesis in the nucleus/nucleolus; the pentose phosphate pathway for nucleotide synthesis in the cytosol [ 125 ]; de novo lipid and sterol synthesis at the ER [ 125 ]; changes in mitochondrial biogenesis, dynamics and function [ [126] , [127] , [128] ]; and secretory activity at the Golgi [ 129 ].…”
Section: Overview Of Organelle Communication Pathwaysmentioning
confidence: 99%
“…Interestingly, GRASP55 has also recently been found to be a substrate of mTORC1, a major sensor and initiator of autophagy. The inhibition of mTORC1 induced the de-phosphorylation of GRASP55 and its re-localization to multivesicular bodies (MVBs), where GRASP55 likely plays a role in exosome secretion [ 66 ].…”
Section: Autophagy and The Golgi Apparatusmentioning
confidence: 99%